Synergism Study of the Alkalo Bacterial Biculture Consortium Thermophilic from Sapan River Aro Hot Springs - Mochammad Asshydiqie Syadza Althaf (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Thermophilic bacteria are microbes that have the potential to produce heat-stable or thermostable enzymes ranging from 45-70 °C. So that thermophilic bacteria have a number of advantages in their use in the industrial sector which generally uses high temperatures. This study aims to examine the compatibility of thermophilic bacterial isolates. This research is descriptive using the pouring method (Pour Plate Method). The results showed that the thermophilic bacterial isolates tested (SSA- 8, SSA- 16, SSA- 14, SSA- 1, SSA-3 dan SSA- 12) and all their compatible partners were seen with no inhibition zones.